Evaluating the Efficacy of Primary Treatment for Graves’ Disease Complicated by Thyrotoxic Periodic Paralysis - Rita Yuk-Kwan Chang; Brian Hung-Hin Lang; Ai Chen Chan; Kai Pun Wong (International Journal of Endocrinology)
Objective. Thyrotoxic periodic paralysis (TPP) is a potentially life-threatening complication of Graves’ disease (GD). The present study compared the long-term efficacy of antithyroid drugs (ATD), radioactive iodine (RAI), and surgery in GD/TPP. Methods. Sixteen patients with GD/TPP were followed over a 14-year period. ATD was generally prescribed upfront for 12–18 months before RAI or surgery was considered. Outcomes such as thyrotoxic or TPP relapses were compared between the three modalities. Results. Eight (50.0%) patients had ATD alone, 4 (25.0%) had RAI, and 4 (25.0%) had surgery as primary treatment. Despite being able to withdraw ATD in all 8 patients for 37.5 (22–247) months, all subsequently developed thyrotoxic relapses and 4 (50.0%) had ≥1 TPP relapses. Of the four patients who had RAI, two (50%) developed thyrotoxic relapse after 12 and 29 months, respectively, and two (50.0%) became hypothyroid. The median required RAI dose to render hypothyroidism was 550 (350–700) MBq. Of the 4 patients who underwent surgery, none developed relapses but all became hypothyroid. Conclusion. To minimize future relapses, more definitive primary treatment such as RAI or surgery is preferred over ATD alone. If RAI is chosen over surgery, a higher dose (>550 MBq) is recommended.